Analisa Penerapan Resapan Biopori Pada Kawasan Rawan Banjir Di Kecamatan Telaga Biru - Ilyas Ichsan; Zulkifli S. Hulalata (Gorontalo Journal of Infrastructure and Science Engineering, 2018)
Surface Runoff occurs due to high rainfall that falls in an area that is able to caused flooding. Infiltration Biopori Technology serves to reduce storm water runoff is to increase the water absorbing soil thus reducing surface runoff that often causes floods. This research aim was to get the value of infiltration without biopori infiltration and infiltration with infiltration biopori, as well as obtaining the presentation of discharge runoff can be reduced by 1 piece infiltration biopori on a plot of land with an area of 100 m2. The research methods used quantitative methods. Primary data obtained from testing on-site infiltration studies used Single Tool Infiltrometer Ring with a diameter of 25 cm, were analyzed used the method of Horton Curve. Secondary data, precipitation last 10 years from the year 2006 to 2015 obtained from BMKG Djalaludin Gorontalo Airport consists of three stations that BPP-Tapa, Talumelito, Slamet Djalaludin Gorontalo, then analyzed used rational methods to obtain discharge of the runoff. Analysis of the results obtained, infiltration without absorption biopori was 4.5 cm / hour, once created biopori infiltration infiltration rate rose to 38.1 cm / hour, and 1 absorption biopori on a plot of land with an area of 100 m2 can reduce runoff discharge at 10.82%